The Effectiveness of the Games Based Learning Model Using LUAK Game Media (Physics Kid’s Ludo) on Understanding Concepts in the Material on Climate Change and Global Warming - Gunawan, Selma Dwi Utami; Karim, Saeful; Aviyanti, Lina (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2024)
This study aims to improve students' conceptual understanding by implementing a game based learning model using the LUAK (Ludonya Anak Fisika) game media on climate change and global warming material. Concept understanding data were collected through a test using a pre-experimental method with a One Group Pretest-Posttest design involving one class in class X with a total of 36 students, but the researcher only used 32 students because 4 students had other roles to help researchers in conducting treatment in class. Then the data analysis techniques used were N-Gain analysis and effect size analysis. Hypothesis testing used normality test, homogeneity test, and Wilcoxon test (non-parametric test). The results showed that the class that applied the game based learning model using the LUAK (Ludonya Anak Fisika) game media had an N-Gain value of understanding ability of <g> = 0.54 which was included in the moderate category. Meanwhile, the calculation result of Effect Size of understanding ability with a value of 2.22 which is included in the very high category. Thus, the application of game based learning model is considered effective for understanding ability in climate change and global warming material. Additionally, students provided positive feedback after using this game-based learning model.